Penerapan Syariat Islam terhadap Peraturan Daerah dalam Sistem Hukum Nasional Indonesi - Yunus, Nur Rohim (Hunafa: Jurnal Studia Islamika, 2015)
The application of sharia in Indonesia has a strong historical roots, even predates the history of European law itself. So if there is a desire of some parties to implement it, it is not something fabricated or new demands are groundless,but already has a strong historical roots with the age of the nation.Therefore, the national law system opens opportunity to adopt islamic shariat becoming national law, like what had been implemented, zakat constitution, marriage, and so forth. In other hand, it opens an opportunity to the local government to implement the islamic shariat for local constitution and it can implement to the local society interest.